The Ground Control Station Design For Can-Sized Satellite (CanSAT) System - Noor Thuwaibah Abdul Razak; Huda A Majid; Faiz Asraf Saparuddin; Muhamad Fitry Abdul Jalil; Muhamad Shakry Jamaluddin Jalil; Mohd Hazmi Mokhtar (Institute for Research on Innovation and Industrial System (IRIS), 2020)
Nowadays, Natural disaster tragedy is now one of the world's biggest concerns. Can-sized satellite, MedSAT: Location-Aware CanSAT for On-Site Emergency Medical Supplies develop a platform for finding direction and accurately locating an emergency patient and providing emergency medical supplies such as bandages, antiseptic wipes, sterile gauze pads of various sizes, insulin, pills, syringe and antivenom, as well as real-time visual feed for medical diagnosis during and after landing. This project focuses on the design of MedSAT and provides a real-time system to capture MedSAT’s real-time data during descent. The objective of the real-time system is to improve the accuracy and location speed of MedSAT data collection which can provide readings of altitude, latitude and longitude to help MedSAT navigate to the patient location. Hardware design (flight controller, GPS module and telemetry kit), software design (Mission Planner) and real-time system (RTS) are the main components of this platform. In addition, the ground station was developed to communicate with users via wireless telemetry communication using MAVLink protocol. Based on the overall findings, MedSAT and ground station's compact and lightweight design was developed in search and rescue operations for emergency location.